2021
DOI: 10.1111/apha.13694
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3 and TRPV4 as candidate proteins for intestinal ammonium absorption

Abstract: Aim Absorption of ammonia from the gut has consequences that range from encephalitis in hepatic disease to global climate change induced by nitrogenous excretions from livestock. Since patch clamp data show that certain members of the transient receptor potential (TRP) family are permeable to NH4+, participation in ammonium efflux was investigated. Methods Digesta, mucosa and muscular samples from stomach, duodenum, jejunum, ileum, caecum and colon of pigs were analysed via colourimetry, qPCR, Western blot, im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 81 publications
(276 reference statements)
2
22
1
Order By: Relevance
“…In protein from a model of human keratinocytes (human skin equivalent, 12 replicates from 2 donors), the ~ 95 kDa band was weak, requiring high exposure times. The intense band at ~ 60 kDa may correspond to a previously described splice variant first reported in human keratinocytes [74] but also found in bovine rumen [39], porcine intestine, and porcine and murine skin [46] or to a degradation product.…”
Section: Immuno-detection Of Htrpv3supporting
confidence: 55%
See 4 more Smart Citations
“…In protein from a model of human keratinocytes (human skin equivalent, 12 replicates from 2 donors), the ~ 95 kDa band was weak, requiring high exposure times. The intense band at ~ 60 kDa may correspond to a previously described splice variant first reported in human keratinocytes [74] but also found in bovine rumen [39], porcine intestine, and porcine and murine skin [46] or to a degradation product.…”
Section: Immuno-detection Of Htrpv3supporting
confidence: 55%
“…In our previous study of the rumen [39] and in an unrelated study of cultured keratinocytes [74], the ~ 60 kDa band was also stronger than the ~ 95 kDa band, although the difference in staining intensity was not as pronounced. Furthermore, we observed that the ~ 60 kDa band was always more pronounced than the ~ 95 kDa band in various parts of the porcine intestine, the porcine skin and in murine skin [46]. While this band may reflect a breakdown product, sequences for a ~ 60 kDa splice variant of TRPV3 are available for the bovine species (AAI46079.1) and for mice (XP_006533411.1) and suggest that the protein is truncated after amino acid 527 (mouse) or 526 (bovine) (for alignment, see the supplement of [46]).…”
Section: Detection Of the Proteinmentioning
confidence: 72%
See 3 more Smart Citations